Interactions between oral antineoplastic agents and concomitant medication: a systematic review. (May 2013) - Carcelero, Esther; Anglada, Helena; Tuset, Montse; Creus, Natalia
<x xml:space="preserve">Abstract</x> Introduction: In recent years, the number of oral antitumoral agents has considerably increased. Oral administration increases the risk of interactions, because most oral anticancer drugs are taken on a daily basis. Interactions can increase exposure to antitumoral agents or cause treatment failure. Many antitumoral drugs undergo enzymatic metabolism by cytochrome P450. As some act as inducers or inhibitors of one or more isoenzymes, they can lead to decreases or increases in plasma concentrations of concomitant drugs. Hence, cytostatic drugs can act not only as victims but also as perpetrators. P-glycoprotein, an efflux transporter, can also be involved in pharmacokinetic interactions. Areas covered: A Medline search was performed to summarize the available evidence of the most clinically relevant interactions between oral chemotherapy agents and other drugs. The search covered the period from 1966 until August 2012 for each antitumoral drug using the medical subject headings 'Drug Interactions' OR 'Pharmacokinetics'. While the present review is not exhaustive, it aims to increase clinicians' awareness of potential drug–drug interactions. Expert opinion: As cancer patients are often polymedicated and treated by different physicians, the risk of drug interactions between antitumoral agents and other medications is high. More clinical interaction studies are encouraged to ensure appropriate antineoplastic pharmacokinetics in clinical practice.